PELATIHAN PERANGKAT LUNAK PERKANTORAN SEBAGAI UPAYA PENGELOLA DALAM MENINGKATKAN LIFE SKILL WARGA BELAJAR PAKET C - Elvira Berliani; Dinno Mulyono (IKIP Siliwangi, 2023)
This research is backgrounded by data that states that residents learn Package C at PKBM Bhina Swakarya, there are still learning residents who do not understand how to operate a computer, especially in operating office software such as Microsoft Word and Microsoft PPT. Meanwhile, computer life skills are needed for citizens to learn in the face of ANBK , UN and the provision of skills they have after graduation. The theories used in this study include training theory, life skills theory, and the theory of the Center for Community Learning Activities (PKBM). The method used is a qualitative approach with qualitative descriptive research methods. Data collection techniques use interview and observation techniques. The subjects of the study were one manager, one tutor, and three residents studying package C at PKBM Bhina Swakarya Batujajar. The results of research on office software training as an effort by managers in improving the life skills of residents learning package C can be said that the manager has been able to carry out the implementation process well, so that the results obtained from life skills training run well and are in accordance with expectations. This can be seen from the increase in citizens learning package C in the use and operation of computers, especially the operation of Microsoft Word and Microsoft PPT.